2005
DOI: 10.1002/cne.20487
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural analysis of projections to the pulvinar nucleus of the cat. II: Pretectum

Abstract: The pretectum (PT) can supply the pulvinar nucleus (PUL), and concomitantly the cortex, with visual motion information through its dense projections to the PUL. We examined the morphology and synaptic targets of pretecto-pulvinar (PT-PUL) terminals labeled by anterograde transport in the cat. By using postembedding immunocytochemical staining for γ-aminobutyric acid (GABA), we additionally determined whether PT-PUL terminals or their postsynaptic targets were GABAergic. We found that the main projection from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 40 publications
(102 reference statements)
0
15
0
Order By: Relevance
“…Several studies have reported pretectal projections to the SC (Baldauf, Wang, Chomsung, & May, ; Baldauf, Wang, Wang, & Bickford, ; Born & Schmidt, ; Sudkamp & Schmidt, ; Weber & Harting, ; Weber, I‐Li Chen, & Hutchins, ). In the cat, Baldauf et al () described bilateral projections from the PPT to the SGS and SZ.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported pretectal projections to the SC (Baldauf, Wang, Chomsung, & May, ; Baldauf, Wang, Wang, & Bickford, ; Born & Schmidt, ; Sudkamp & Schmidt, ; Weber & Harting, ; Weber, I‐Li Chen, & Hutchins, ). In the cat, Baldauf et al () described bilateral projections from the PPT to the SGS and SZ.…”
Section: Discussionmentioning
confidence: 99%
“…To reveal the distribution of GAD, sections were processed using immunocytochemical protocols previously described (Bickford et al, 1999; Baldauf et al, 2005). To reveal the distribution of vGLUT1 and vGLUT2, 50-μm-thick vibratome sections were preincubated in 10% NGS in PBS for 30 minutes and then incubated overnight at 4°C in solutions containing dilutions of the anti-vGLUT1 or anti-vGLUT2 antibodies.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the GABAergic terminals labeled following larger injections likely represent pretectopulvinar terminals (Baldauf et al, 2005), particularly insofar as more GABAergic terminals were labeled following injections in the most rostral SC. Therefore, we confined our analysis to the synaptic targets of non-GABAergic BDA-labeled terminals.…”
Section: Distribution Of Vglut and Gad In The Pulvinar Nucleusmentioning
confidence: 99%
“…cortex; thalamus; visual system; sensorimotor; ultrastructure The feline pulvinar nucleus (PUL) receives input from a wide array of cortical areas (Raczkowski and Rosenquist, 1983) as well as the pretectum (PT;Berman, 1977;Berson and Graybiel, 1978;Schmidt et al, 2001;Baldauf et al, 2005). However, the contribution of these inputs to the response properties of PUL neurons is unknown.…”
Section: Indexing Termsmentioning
confidence: 99%
“…The goal of this study was to examine the synaptic arrangements of parietopulvinar terminals, and the laminar distribution of parietopulvinar cells, as a first step toward understanding how cortical inputs may influence the response properties of PUL neurons. In the accompanying paper, we describe the synaptic arrangements and cells of origin of the pretectal input to the PUL (Baldauf et al, 2005). …”
mentioning
confidence: 99%